A rapid-crosslinking antimicrobial hydrogel with enhanced antibacterial capabilities for improving wound healing - Zhang, Xi; Li, Wanxin; Wei, Genying; Yan, Yuling; He, Ruitao; Wang, Yan; Chen, Daoyuan; Qin, Xiaofei (Frontiers in Physiology, 2023)
One of the main reasons impeding wound healing is wound infection caused by bacterial colonization with a continuous stage of inflammation. Traditional wound treatments like gauze are being replaced by tissue adhesives with strong wet tissue adhesion and biocompatibility. Herein, a fast-crosslinking hydrogel is developed to achieve both strong antimicrobial properties and excellent biocompatibility. In this study, a simple and non-toxic composite hydrogel was prepared by the Schiff base reaction between the aldehyde group of 2,3,4-trihydroxybenzaldehyde (TBA) and the amino group of ε-Poly-L-lysine (EPL). Subsequently, a succession of experiments toward this new hydrogel including structure characterization, antimicrobial properties, cell experiment and wound healing were applied. The results of the experiments show that the EPL-TBA hydrogel not only exhibited excellent contact-active antimicrobial activities against Gram-negative bacteria Escherichia coli (E. coil) and Gram-positive Bacteria Staphylococcus aureus (S. aureus), but also inhibited the biofilm formation. More importantly, the EPL-TBA hydrogel promoted the wound healing with low cytotoxicity in vivo. These findings indicate that the EPL-TBA hydrogel has a promising use as a wound dressing in the bacterial infection prevention and wounds healing acceleration.